2023
DOI: 10.1007/s10592-023-01507-4
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics identifies barriers to Natterjack toad metapopulation dispersal

Abstract: Habitat fragmentation and loss reduce population size and connectivity, which imperils populations. Functional connectivity is key for species persistence in human-modified landscapes. To inform species conservation management, we investigated spatial genetic structure, gene flow and inferred dispersal between twelve breeding sites of the Natterjack toad (Bufo calamita); regionally Red-Listed as Endangered in Ireland. Spatial genetic structure was determined using both Bayesian and non-Bayesian clustering anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…In addition, the question of whether inference based on population‐based approaches is less affected by the choice of genetic distance metric needs to be investigated. Furthermore, a ResistanceGA ‐based empirical study has recently suggested that convergence of the results obtained with different population‐based genetic distance metrics and AICc‐based model support improved when using a least‐cost path approach, rather than the current flow method implemented here, to calculate resistance distances (Reyne et al, 2023). The study was performed on natterjack toads ( Bufo camalita ) and further research will show whether this conclusion is generally valid or a result of the limited mobility of the study species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the question of whether inference based on population‐based approaches is less affected by the choice of genetic distance metric needs to be investigated. Furthermore, a ResistanceGA ‐based empirical study has recently suggested that convergence of the results obtained with different population‐based genetic distance metrics and AICc‐based model support improved when using a least‐cost path approach, rather than the current flow method implemented here, to calculate resistance distances (Reyne et al, 2023). The study was performed on natterjack toads ( Bufo camalita ) and further research will show whether this conclusion is generally valid or a result of the limited mobility of the study species.…”
Section: Discussionmentioning
confidence: 99%